Structural dynamics of propeller loop: towards folding of RNA G-quadruplex - Havrila, Marek; Stadlbauer, Petr; Kührová, Petra; Banáš, Pavel; Mergny, Jean-Louis; Otyepka, Michal; Šponer, Jirí (Nucleic acids research, 2018)
We have carried out an extended set of standard and enhanced-sampling MD simulations (for a cumulative simulation time of 620 μs) with the aim to study folding landscapes of the rGGGUUAGGG and rGGGAGGG parallel G-hairpins (PH) with propeller loop. We identify folding and unfolding pathways of the PH, which is bridged with the unfolded state via an ensemble of cross-like structures (CS) possessing mutually tilted or perpendicular G-strands interacting via guanine-guanine H-bonding. The oligonucleotides reach the PH conformation from the unfolded state via a conformational diffusion through the folding landscape, i.e. as a series of rearrangements of the H-bond interactions starting from compacted anti-parallel hairpin-like structures. Although isolated PHs do not appear to be thermodynamically stable we suggest that CS and PH-types of structures are sufficiently populated during RNA guanine quadruplex (GQ) folding within the context of complete GQ-forming sequences. These structures may participate in compact coil-like ensembles that involve all four G-strands and already some bound ions. Such ensembles can then rearrange into the fully folded parallel GQs via conformational diffusion. We propose that the basic atomistic folding mechanism of propeller loops suggested in this work may be common for their formation in RNA and DNA GQs.
Keywords: RNA Folding; sekvence nukleotidů; termodynamika; Molecular Dynamics Simulation; Base Sequence; kinetika; G-kvadruplexy; simulace molekulární dynamiky; vodíková vazba; RNA; sbalování RNA; guanin; Guanine; Hydrogen Bonding; Kinetics; G-Quadruplexes; Thermodynamics